Pectin - Rodrigues, Célia Fortuna (2015)
Pectin is a family of complex polysaccharides that occur as structural materials in all land-growing plants. Its main utilization is on the food industry mainly due to his gelling properties. Recently, pectin has been exploited for different biomedical applications namely for drug delivery and for tissue engineering. This chapter will discuss the chemistry and gelling formation mechanism and properties of pectin. Furthermore health aspects of pectin are overviewed as well as diverse current and emerging applications in the biomedical field.